A new approach for an ultrasensitive tactile sensor covering an ultrawide pressure range based on the hierarchical pressure-peak effect. Issue 3 (17th December 2019) - Wu, Congyi; Zhang, Tian; Zhang, Jian; Huang, Jin; Tang, Xing; Zhou, Tingting; Rong, Youmin; Huang, Yu; Shi, Songxin; Zeng, Dawen
Abstract : Flexible tactile sensors that imitate the skin tactile system have attracted extensive research interest due to their potential applications in medical diagnosis, intelligent robots and so on. Abstract : Flexible tactile sensors that imitate the skin tactile system have attracted extensive research interest due to their potential applications in medical diagnosis, intelligent robots and so on. However, it is still a great challenge to date to fabricate tactile sensors with both high sensitivity and wide detection range due to the difficulties in modulating the resistance variation in the sensing materials in a wide pressure range. Here, a tactile sensor with a novel design based on the hierarchical pressure-peak effect (HPPE) consisting of PVP nanowires and electroless deposition (ELD) silver PDMS micro-pyramids is reported. The HPPE can effectively modulate the resistance change rate by adjusting the change of contact area during compression deformation, and the HPPE tactile sensor was demonstrated to have both ultrahigh sensitivity (11.60–1108.75 kPa −1 ) and ultrawide pressure range (0.04–600 kPa). The designed HPPE tactile sensor is successfully utilized in detecting multi-level pressures including respiration, finger heart rate, pulse and foot pressures. Moreover, it is used to sense a subtle clamping force in the Leonardo Da Vinci surgical robot demonstrating the potential of the sensor in surgical robot applications. In all these cases, the sensor exhibits enough capability to respond quickly to ultrawide-range pressures with high accuracy and stability.